2000
DOI: 10.1590/s0102-33062000000200003
|View full text |Cite
|
Sign up to set email alerts
|

Contagens cromossômicas em espécies brasileiras de Paspalum L. (Gramineae)

Abstract: RESUMO -(Contagens cromossômicas em espécies brasileiras dePaspa/um L. (Gramineae».A partir de coletas de germoplasma de espécies de Paspa/um, realizadas nas cinco regiões do Brasil, e subseqüentes análises citológicas em mitose ou meiose, reportam-se os números de cromossomos de 107 acessos, distribuídos por 33 espécies, representativas de 13 dos grupos taxonômicos informais em que o gênero é tradicionalmente subdividido. No grupo Plicatula, sob intensa revisão taxonômica, 27 acessos são citados ainda sem ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
3
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
8
21
3
8
Order By: Relevance
“…Accurate checking of passport data of the accessions cited by distinct authors (Table 1) confirms the conclusion of Pozzobon et al (2000) that references to 2n = 40 in this species can be traced to ill-identified specimens of P. regnellii Mez.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Accurate checking of passport data of the accessions cited by distinct authors (Table 1) confirms the conclusion of Pozzobon et al (2000) that references to 2n = 40 in this species can be traced to ill-identified specimens of P. regnellii Mez.…”
Section: Introductionsupporting
confidence: 66%
“…Previous tetraploid (2n = 4x = 40) reports for P. conspersum, associated with regular meiosis and sexual reproduction (Fernandes et al, 1974;Burson and Bennett, 1976), do not, in fact, refer to this species. On the contrary, hexaploidy (2n = 6x = 60) has been most commonly reported for true representatives of the species (Quarín, 1977;Quarín and Hanna, 1980;Pozzobon and Valls, 1987;Honfi et al, 1990;Pagliarini et al, 2001;Adamowski et al, 2005;Pozzobon et al, 2000Pozzobon et al, , 2008Hojsgaard et al, 2009). The 60-chromosome race of P. conspersum analyzed by Quarín and Hanna (1980) showed regular meiosis, with primarily bivalent pairing and a low percentage of univalents and quadrivalents.…”
Section: Cytogenetics Of P Conspersummentioning
confidence: 99%
“…In line with additional papers that cover a broader sampling, both in terms of accessions and geographical sites of origin of available Paspalum germplasm (HONFI et al, 1990;POZZOBON et al, 2000;MORRONE et al, 2006;HOJSGAARD et al, 2009), they document the fi nding of more than a single ploidy level in distinctive accessions of same species.…”
Section: ---------------------Average/cmp (Range In Parenthesis) ----mentioning
confidence: 62%
“…Anachyris (MORRONE et al, 2000). Chromosome numbers of 2n=40 and 2n=60 were known for the species, the tetraploids being largely the most common (BURTON, 1940;GOULD, 1975;BURSON & HUSSEY, 1998;POZZOBON et al, 2000;PAGLIARINI et al, 2001).…”
Section: Species Counted For the First Timementioning
confidence: 99%